TOLERANCE AS AN EXHIBITION OF HUMANISM FOR THE RISING GENERATION - Marchenoka, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The mankind is going the way of the fast scientific and technological progress, at the same time feeling shortage of respect, kindness, and mutual understanding in this global process. The modern scientific and technical progress is leaving behind the moral or ethical progress stimulating emergence of new forms of spiritual impoverishment, cruelty, violence and hostility. The best humanistic principles, which are based on mutual aid, sympathy are depreciating, blurring the very concept of the moral. The situation gives evidence of the process of dehumanisation of the society, when the person’s value becomes lower than other values.The relevance of examination of tolerance in the aspect of humanisation is determined by the society’s demand for development of relations of a new type, which would be grounded on humanistic base, where every person is regarded as the highest value, where there is a priority of general human values against ethnic values, where the basic principle of people’s relations are: benevolence, humanity, mercy and respect.